Perspectives on Behavior-Based versus Outcome-Based Salesforce Control Systems - Anderson, Erin; Oliver, Richard L. (Journal of Marketing, 1987)
Forms of control systems used in salesforce evaluation and based on the monitoring of outcomes or of behaviors are described, contrasted, and evaluated in terms of emerging theories in economics, organization theory, and cognitive psychology. Generally, the principles of behavior control as opposed to outcome control are found to be consistent with these theoretical perspectives with exceptions as noted, though studies of descriptive trends suggest that outcome control remains useful as a sales management philosophy. The authors conclude with a set of propositions intended to stimulate research on the managerial and behavioral consequences of the two control philosophies.